ChemInform Abstract: Zinc‐Catalyzed Multicomponent Reactions: Easy Access to Furyl‐Substituted Cyclopropane and 1, 2‐Dioxolane Derivatives. Issue 41 (September 2016) - Mata, Sergio; Gonzalez, Jesus; Vicente, Ruben; Lopez, Luis A.
Abstract: A convenient synthesis of cyclopropyl‐substituted furan derivatives by a zinc‐catalyzed three‐component coupling of 1, 3‐dicarbonylic compounds, 2‐alkynals and alkenes is reported.